2020
DOI: 10.1002/lary.28544
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Croup and Gastroesophageal Reflux: A Systematic Review and Meta‐Analysis

Abstract: Objective The mechanism by which recurrent croup occurs is unknown. Gastroesophageal reflux is commonly implicated, although this relationship is only loosely documented. We conducted a systematic review with a meta‐analysis component to evaluate the relationship between recurrent croup and gastroesophageal reflux disease (GERD), and to assess for evidence of improvement in croup symptoms when treated. Style Design Systematic Review and Meta Analysis. Methods We searched five separate databases. Studies were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…13,15,16,[18][19][20][21][22][23][24] For example, a high incidence of gastroesophageal reflux disease has been reported in patients diagnosed with recurrent croup, with many of these patients experiencing symptom resolution with antireflux medication. 16,25 In our study, a diagnosis of gastroesophageal reflux disease was reported in 27 (23.7%) patients. Reflux-associated laryngotracheal mucosal irritation may cause croup-like respiratory symptoms.…”
Section: Symptom Characteristics Of Recurrent Croupmentioning
confidence: 50%
“…13,15,16,[18][19][20][21][22][23][24] For example, a high incidence of gastroesophageal reflux disease has been reported in patients diagnosed with recurrent croup, with many of these patients experiencing symptom resolution with antireflux medication. 16,25 In our study, a diagnosis of gastroesophageal reflux disease was reported in 27 (23.7%) patients. Reflux-associated laryngotracheal mucosal irritation may cause croup-like respiratory symptoms.…”
Section: Symptom Characteristics Of Recurrent Croupmentioning
confidence: 50%
“…The rate of positive airway findings in children undergoing DLB for RC symptoms ranges between 33%-55% in different studies 23,24,30 have been associated with GERD include erythema and edema of the arytenoids or posterior glottis or narrowing or strictures of the esophagus. 33,34 It is proposed that aspiration of refluxed acid into the trachea and upper airway causes mucosal sloughing and edema that makes the patient more susceptible to RC symptoms.…”
Section: Airway Findingsmentioning
confidence: 99%
“…The rate of positive airway findings in children undergoing DLB for RC symptoms ranges between 33%–55% in different studies 23,24,30 Among these, various grades of subglottic narrowing/stenosis and clinical findings suggestive of GERD are the leading abnormal findings. Sub‐glottic stenosis is generally Grade I or II (Myer‐Cotton grading system based on endotracheal tube size).…”
Section: Role Of Triple Endoscopy In CCmentioning
confidence: 99%
See 1 more Smart Citation
“…Причини виникнення рекурентних епізодів ГОЛ можуть бути різними: аномалії розвитку гортані, інтубація трахеї в анамнезі, гастро езофагеальний рефлюкс, первинне тубінфіку вання, бронхіальна астма, інші алергічні захво рювання, імунологічні порушення, генетична схильність, рецидивні ГРІ тощо [4,5,11,16,22,25]. Зазначені чинники ризику можуть також призводити до атипового перебігу крупу.…”
unclassified